Extracorporeal membrane oxygenation in adults: A brief review and ethical considerations for nonspecialist health providers and hospitalists. Issue 12 (21st October 2014) - Meltzer, Ellen C.; Ivascu, Natalia S.; Acres, Cathleen A.; Stark, Meredith; Kirkpatrick, James N.; Paul, Subroto; Sedrakyan, Art; Fins, Joseph J.
<x xml:space="preserve">Abstract</x> Given the pace, distribution, and uptake of technological innovation, patients experiencing respiratory failure, heart failure, or cardiac arrest are, with greater frequency, being treated with extracorporeal membrane oxygenation (ECMO). Although most hospitalists will not be responsible for ordering or managing ECMO, in‐hospital healthcare providers continue to be a vital source of patient referral and, accordingly, need to understand the rudiments of these technologies so as to co‐manage patients, counsel families, and help ensure that the provision of ECMO is consistent with patient preferences and appropriate goals of care. In an effort to prepare hospitalists for these clinical responsibilities, we review the history and technology behind modern‐day ECMO, including venoarterial extracorporeal membrane oxygenation (VA‐ECMO) and venovenous extracorporeal membrane oxygenation. Building upon that foundation, we further highlight special ethical considerations that may arise in VA‐ECMO, and present an ethically grounded approach to the initiation, continuation, and discontinuation of treatment. Journal of Hospital Medicine 2014;9:808–813. © 2014 Society of Hospital Medicine